The development of a computerized cueing device to help people with dementia to be more independent. - Mihailidis A; Fernie GR; Cleghorn WL (Technology & Disability, 2000)
Many people with dementia have difficulty completing activities of daily living (ADL) independently and require constant assistance and supervision. This results in a loss of independence and privacy, and causes them to become embarrassed and agitated. It was hypothesized that independence might be restored by using a computerized device that prompts and monitors a person as he or she completes an activity. Thus, assistance is provided, but a caregiver is not required to be present.A prototype of such a device was developed, and a pilot study was conducted with one subject who had severe dementia. The handwashing activity was selected as the ADL for this study. It was found that the subject's performance improved when the device was used, and that the subject had fewer interactions with his caregiver. The pilot study also identified improvements that should be incorporated into future computerized devices and clinical trials.